AN ANALYSIS OF BIOGRAPHICAL FILMS OF THE IMPORTANT FIGURE IN BUDDHISM - Nildasri , Phra Wutthikrai; Chermanchonlamark, Chalongrat (Journal of MCU Buddhapanya Review, 2025)
The objective of “An Analysis of Biographical Films of The Important Figure in Buddhism” aimed to investigate the narrative strategies used in the biographical film of important Buddhist figures in the “Krua Toh the Immortal Monk of Rattanakosin”. The study was conducted through textual analysis based on qualitative methodology. The research results found that: 1) In terms of plot, five stages were found as follows: exposition, rising action, climax, falling action, and ending 2) In term of theme, that used the pure love of family, the truth of love, impermanence, believe and faith in Buddhism, and teacher spirituality. 3) In term of character, the main characters and the subordinate characters were found. 4) In terms of conflict, it was found conflict between person and person. 5) In terms of point of view, that used the objective narrator. And 6) In terms of scene, it was found that most scenes were mainly associated with nature, artificial, and characters’ ways of living.